Altitudinal gradients in Magellanic sub-Antarctic lagoons: the effect of elevation on freshwater macroinvertebrate diversity and distribution - Rendoll Carcamo, Javier; Contador Mejias, Tamara Andrea; Ganan, Melisa; Perez Troncoso, Carolina; Maldonado Marquez, Alan; Convey, Peter; Kennedy, James; Rozzi Marin, Ricardo Roberto (My University, 2019)
Background. The study of attitudinal gradients provides insights about species diversity, distribution patterns and related drivers. The Magellanic sub-Antarctic ecoregion has a steep elevational gradient, peaking at around 1,000 m a.s.l., and marked changes in temperature and landscape composition can be observed over relatively short distances. Methods. This study assessed freshwater macroinvertebrate diversity associated with lakes and ponds along the altitudinal gradient of a Magellanic sub-Antarctic watershed. Results. A monotonic decline in species richness was observed with increasing elevation, with simpler and more even community composition at higher altitude. This pattern differs from the mid-peak trend found in streams of the same watershed. Functional feeding group structure also diminished with increasing elevation. Discussion. The study provides a descriptive baseline of macroinvertebrate community structure associated with lentic freshwater ecosystems in the Magellanic sub-Antarctic ecoregion, and confirms that elevation has substantial effects on community structure, function and environmental features, even in these relatively low elevation mountain ranges. The harsh environmental conditions of this ecoregion increase freshwater macroinvertebrate development time, as well as decreasing habitat availability and food supply, supporting simple but well adapted communities. In conjunction with previous research, this study provides a watershed-scale platform of information underpinning future long-term research in the region.
Keywords: elevation gradient; sub-antarctic; littoral invertebrates; lakes; southern chile